Multidisciplinarity as an interdisciplinary aspect - Gonçalves, João Carlos; Cantino, Roberta Cristina Gonçalves; Moura, Rosilene da Silva (Revista Coleta Científica, 2017)
The scope of this editorial is to discuss multidisciplinarity as an interdisciplinary aspect. We know that an editorial product that interrelates interlacing the knowledge constitutes interdisciplinarity. However, several themes from different areas composing a single multidisciplinary product also constitute an interdisciplinary editorial product. There are even authors who do not distinguish multidisciplinarity from interdisciplinarity. This first issue of Coleta Científica journal brings exactly this multidisciplinary and interdisciplinary proposal. The four articles that inaugurate the journal bring together